(untitled) (Baghdad Science Journal, 2024)
Proteus mirabilis is considered as a third common cause of catheter-associated urinary tract infection, with urease production, the potency of catheter blockage due to the formation of biofilm formation is significantly enhanced. Biofilms are major virulence factors expressed by pathogenic bacteria to resist antibiotics; in this concern the need for providing new alternatives for antibiotics is getting urgent need, This study aimed to explore whether green synthesized zinc oxide nanoparticles (ZnO NPs) can function as an anti-biofilm agent produced by P.mirabilis. Bacterial cells were capable of catalyzing the biosynthesis process by producing reductive enzymes. The nanoparticles were synthesized from cell free extract of P.mirabilis. Characterization of biosynthesized zinc nanoparticles was carried out to determine the chemical and physical properties of the product using AFM, TEM, FESEM, XRD and UV visible spectrometry. The hexagonal structure was confirmed by XRD, Particle size was marked at 84.45 nm by TEM, FESEM was used to confirm the surface morphology. AFM analysis was used to reveal the roughness and distribution of nanoparticles. UV–visible spectra of the synthesized nanoparticles recorded maximum peak at 287 nm. Zinc nanoparticles showed remarkable biofilm inhibitory effect on clinical isolates of multidrug resistant Proteus mirabilis. Strong biofilm producer strains show weak biofilm production After incubation for 24 and 48 hours at 37Co with 32 μg/ml sub -MIC concentration of ZnO nanoparticles. Down regulation changes in LuxS expression using Real time PCR technology were detected after treatment with zink nanoparticles of these isolates compared to untreated isolates. From all findings conducted by this study, zinc oxide nanoparticles can function as anti-bacterial agent in concentration dependent manner.